Coagulation-Flocculation of Leachate by Using Single Coagulant Made from Chemical Coagulant (Polyaluminium Chloride) and Natural Coagulant (Tapioca Flour) - Mohd Zin, Nur Shaylinda; Ramarao, Taruunen; Zainal Abidin, Mohd Hazreek; Wan Mohamed, Wan Afnizan (International Journal of Integrated Engineering, 2019)
Application of coagulation and flocculation in leachate treatment is common nowadays. Chemical coagulant is commonly applied compared to natural coagulant. Thus, this study compared the effectiveness of landfill leachate treatment by single coagulant which are chemical and natural coagulant through the removal of suspended solid (SS), sludge settling rate and sludge volume index. The experiment was carried out using standard jar test method and raw leachate sample was collected from Landfill Simpang Renggam. The chemical coagulant used was polyaluminium chloride and natural coagulant was Tapioca flour. Tapioca flour has characteristic as coagulant where it has sticky characteristic that can remove pollutant in leachate without leaving any side effects latter and it is available in abundance, cheaper, and environmentally friendly. Result of this study shown that, the optimum dosage and pH of PAC was 3g/L at pH 8 and for tapioca flour was 1g/L at pH 4. The percentage removal by PAC as in term of removal of suspended solid, sludge volume index and sludge settling rate were 94%, 5273 mL/gm and 1.58 cm/min, respectively. While, for tapioca flour there was minimal sludge formation and the removal of SS was 13.3%. The particles size for sludge leachate after treatment for optimum dose was in range of 20Âµm and the floc were arranged compacted, and shaped elongated. Hence, this study shows that PAC is more effective than Tapioca flour as single coagulant in terms of sludge volume index, sludge settling rate, removal of suspended solid and particle size of sludge.